The Impact of Application Effect 0f Application of Cooperative Script learning model on the learning Outcomes of Al-Qur’an and Hadist For 7th Grade Students At Islamic Junior High School Mantingan Ngawi - Hibatul Wafi; Milatul Fatkhiyah (At-Ta'dib, 2021)
The Qur'an is part of the subjects of Islamic religious education given to understand and practice the Qur'an so that it is able to read fluently, translate, infer the contents, copy and memorize selected verses and understand and practice the chosen hadiths. But in this era of globalization, the learning of the Qur'an hadith is considered very low, it is evident that many students do not understand the material of the Quran hadith properly and correctly, especially in implementing it in everyday life, it is due to the lack of interest in learning students of Qur'an hadith material due to learning methods that tend to be less active and boring that result in students' learning outcomes for low Qur'anic hadith material. this research aims to find out the effect of the application of cooperative script learning models on learning outcomes in Qur'an lessons hadith of class VII students in MTs Miftahul Jannah to increase student knowledge, increase student activeness in the learning process so that it can affect learning outcomes. This research uses a quantitative approach, with the design used is true design experiment with design, namely pretest-posttest control group design. Sampling technique using simple random sampling. Then the instruments used in this study researchers use test research instruments. The results of this study show that there is an influence on the application of cooperative script learning model on student learning outcomes in the subjects of the Qur'an hadith. This was shown by the results of the average posttest grade of the experimental class higher than the control class, which was 75.44 for the experiment class and 62.48 for the control class.  As for the results of hypothesis testing (Test T) the results of hypothesis testing obtained data against posttest data of experimental groups and control groups using independent tests T-Test (Test t) with significance results (Sig 2 Tailed) 0.000 < 0.05, then Ho was rejected and H1 accepted, so it can be concluded that the use of cooperative script learning model affects the learning outcomes of Qur'anic hadith subjects.